Analysis of 254 cases of subcutaneous fungal infection (1990-2019) - Jia-hao LI; Jun-hao HUANG; Sha LU; Wen-ying CAI; Jian-chi MA; Li-yan XI; Jun-min ZHANG; Xi-qing LI (editoiral office of Journal of Diagnosis and Therapy on Dermato-venereology, 2020)
Objective: To analyze the clinical, epidemiological and microbiological characteristics of subcutaneous fungal infection occurring in Guangdong, China in the last 30 years. Methods: A 30-year retrospective study from January 1990 to December 2019 reviewing 254 patients with subcutaneous fungal infection from our hospital was conducted. General characteristics, histopathology, diagnosis and isolated strains were analyzed. Results: The average annual diagnosis was 8.47 cases. The average patient age was 47.78 years. The male to female ratio was approximately 1.46∶1. The most common anatomical site of involvement was upper extremities (31.10%).These infections were commonly occured in patients from 31 to 60 years old (46.12%).Sporotrichosis was the most common subcutaneous fungal infection, but the number of infection decreased during recent two decades, while chromoblastomycosis increased in recent decade (P<0.05). Sporothrix globosa was the most common pathogen causing sporotrichosis, and Fonsecaea monophora was the most common agent causing chromoblastomycosis. Conclusions: Sporotrichosis was the most common subcutaneous fungal infection. Based on increasing prevalence of primary and secondary immunodeficiency, the proportion of rare fungal infections has increased in recent decade.Molecular detection methods provide a reliable basis for identifying new pathogens and epidemiological investigation of subcutaneous fungal infection.